Ovarian superstimulation using FSH combined with equine chorionic gonadotropin (eCG) upregulates mRNA encoding proteins involved with LH receptor intracellular signaling in granulosa cells from Nelore cows - Castilho, Anthony C.S. [UNESP]; Nogueira, Marcelo Fábio Gouveia [UNESP]; Fontes, PatrÍcia K. [UNESP]; Machado, Mariana Fernandes [UNESP]; Satrapa, Rafael A. [UNESP]; Razza, Eduardo M. [UNESP]; Barros, Ciro M. [UNESP] (Elsevier, 2014)
The LH plays a key role in controlling physiological processes in the ovary acting via LH receptor (LHR). In general, the effects of LHR on the regulation of granulosa cell differentiation are mediated mainly via the Gs-protein/adenylyl cyclase/cAMP system; however, the LHR activation could also induce phospholipase C (PLC)/inositol trisphosphate (IP3) via Gq/11 system. Additionally, the expression of G-proteins (GNAS, GNAQ, and GNA11) and PLC b has been showed in bovine antral follicle, concomitant with an increase in LHR expression. To gain insight into the effects of superstimulation with FSH (P-36 protocol) or FSH combined with equine chorionic gonadotropin (eCG; P-36/eCG protocol) on the mRNA expression of proteins involved in LHR signaling in bovine granulosa cells, Nelore cows (Bos indicus) were treated with two superstimulatory protocols: P-36 protocol or P-36/eCG protocol (replacement of the FSH by eCG administration on the last day of treatment). Nonsuperstimulated cows were only submitted to estrous synchronization without ovarian superstimulation. The granulosa cells were harvested from follicles and mRNA abundance of GNAS, GNAQ, GNA11, PLCB1, PLCB, PLCB4, and adenylyl cyclase isoforms (ADCY3, ADCY4, ADCY6, ADCY8, and ADCY9) was measured by real-time reserve transcription followed by polymerase chain reaction. No differences on mRNA abundance of target genes were observed in granulosa cells of cows submitted to P-36 protocol compared with control group. However, the cows submitted to P-36/eCG protocol showed upregulation on the mRNA abundance of target genes (except ADCY8) in granulosa cells. Although the P-36 protocol did not regulate mRNA expression of the proteins involved in the signaling mechanisms of the cAMP and IP3 systems, the constant presence of GNAS, GNAQ, GNA11, PLCB1, PLCB3, PLCB4, and adenylyl cyclase isoforms (ADCY3, ADCY4, ADCY6, and ADCY9) mRNA and the upregulation of these genes in granulosa cells from cows submitted to P-36/eCG protocol reinforce the participation of Gq/11/PLC/IP3 signaling as well as Gs-protein/adenylyl cyclase/cAMP system on LHR pathways during bovine granulosa cell differentiation submitted to superstimulatory treatments

TheriogenologyVolume 82, Issue 9, December 2014, Pages 1199 1205

Please cite this article as: Castilho ACS, Nogueira MFG, Fontes PK, Machado MF, Satrapa RA, Razza EM, Barros CM, Ovarian superstimulation using FSH combined with equine chorionic gonadotropin (eCG) upregulates mRNA encoding proteins involved with LH receptor intracellular signaling in granulosa cells from Nelore cows, Theriogenology (2014), doi: 10.1016/j.theriogenology.2014.06.011.
Keywords: Ovary; Superstimulation; LHR; Granulosa cells; Bovine; superstimulation; eCG; Gene expression; granulosa cells; Nelore breed